Efektivitas Teknik Pernapasan Buteyko Dalam Memperbaiki Pola Napas Tidak Efektif Pada Pasien Asma Bronkial - Devinia, Hevita; Wulandari, Tri Suraning; Parmilah, Parmilah (HEALTHY BEHAVIOR JOURNAL, 2025)
Background: Data from the World Health Organization (WHO) shows that around 235 million people suffer from bronchial asthma. Data from the Ministry of Health in 2020 showed that the number of people with bronchial asthma in Indonesia was more than 12 million. Nursing problems that occur in bronchial asthma are ineffective breathing patterns. If ineffective breathing patterns are not addressed properly, the risk of bronchial asthma attacks will increase, the breathing process will become heavier and more difficult, and will even endanger life. One of the non-pharmacological therapies that can applied to patients with bronchial asthma through the buteyko technique. Purpose: This study was to determine the effectiveness of the Buteyko breathing technique in improving ineffective breathing patterns in patients with bronchial asthma. Methods: This case study used 2 respondents with bronchial asthma who experience nursing problems of ineffective breathing patterns aged 43 years and 58 years the method used in this study is a case study design with a qualitative research approach aimed at explaining a phenomenon.The inclusion criteria are respondents who suffer from bronchial asthma, show signs and symptoms of an ineffective breathing pattern, are willing to participate as respondents, and are in the young to middle adult age range (20–59 years). The instruments or tools used in this study to collect data include oximeter, watch/stopwatch, chair, and stethoscope. Results: The results of the analysis showed that after the Buteyko breathing technique was carried out for 3 consecutive days, (dyspnea/shortness of breath, use of breathing aids, prolongation of the expiratory phase, orthopnea/difficulty breathing when lying down, nasal flaring breathing) decreased and the respiratory rate improved. Conclusion: Two respondents initially experienced shortness of breath. After carrying out the Buteyko breathing technique for 3 consecutive days, the breathing pattern improved so that it can be concluded that the Buteyko breathing technique is effective in improving breathing patterns in patients with bronchial asthma.